THE APPLYING CORE STABILITY EXERCISE COMBINATION HEEL RAISES EXERCISE EITHER WITH CORE STABILITY EXERCISE COMBINATION ANKLE STRATEGY EXERCISE ON STATIC BALANCE OF FLAT FOOT 9-11 YEARS OLD CHILDREN IN SEKOLAH DASAR NEGERI 4 TONJA DENPASAR - Witayanti, Made Risma Caesar; Andayani, Ni Luh Nopi; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i03.p08, 2018)
ABSTRACT Flat foot is a flat arch that can disturb the static balance in children aged 9-11 years. Interventions that can be given are core stability exercise, heel raises exercise and ankle strategy exercise. The result of hypothesis test with paired sample t-test on Group Core Stability Exercise combination of Heel Raises Exercise got increase 104,5 seconds with value p = 0,001, while at Group Core Stability Exercise combination of Ankle Strategy Exercise got increase 90,11 seconds with value p = 0.001. Test the difference of two groups increase using independent t-test with p value = 0,031. These results indicate that there is no significant difference in improving the static balance in flat foot children between the two groups. Keywords: Balance, Flat foot, Core Exercise, Heel Raises Exercise, Ankle Strategy Exercise.